Phase formation, piezoelectric, dielectric and mechanical properties of (Pb1-xBax)ZrO3ceramics - G. Rujijanagul (2018)
(Pb1-xBax)ZrO3ceramics for the composition range 0.0 ≤ x ≤ 0.3 were prepared by mixed oxide solid-state reaction method. Phase formation, microstructure, piezoelectric, dielectric and mechanical properties were studies. It was found that the density of the ceramics decreases with increasing amounts of Ba2+, whilst the average grain size is in the range of 1.0-2.3 μm. The structure of as-calcined powder revealed that, the fraction of the orthorhombic phase is decreasing with increasing Ba2+content. The mechanical properties of the ceramics were studied by Vickers and Knoop microhardness testers. The values of Vickers and Knoop hardness are in the range of 4.10-6.48 and 4.15-5.67 GPa respectively. The d33values of the samples increases from ∼0 to 87 pC/N with increasing Ba2+concentration from x = 0.0-0.3. The dielectric constant at room temperature increases with increasing of Ba2+concentration. The results indicated that Ba2+concentration has a significant effect on the electrical properties in PBZ ceramics. © 2006 Elsevier B.V. All rights reserved.